Cyclin D1 is Associated with Radiosensitivity of Triple-Negative Breast Cancer Cells to Proton Beam Irradiation - Choi, Changhoon (Int J Mol Sci, 2019)
Proton therapy offers a distinct physical advantage over conventional X-ray therapy, but its biological advantages remain understudied. In this study, we aimed to identify genetic factors that contribute to proton sensitivity in breast cancer (BC). Therefore, we screened relative biological effectiveness (RBE) of 230 MeV protons, compared to 6 MV X-rays, in ten human BC cell lines, including five triple-negative breast cancer (TNBC) cell lines. Clonogenic survival assays revealed a wide range of proton RBE across the BC cell lines, with one out of ten BC cell lines having an RBE significantly different from the traditional generic RBE of 1.1. An abundance of cyclin D1 was associated with proton RBE. Downregulation of RB1 by siRNA or a CDK4/6 inhibitor increased proton sensitivity but not proton RBE. Instead, the depletion of cyclin D1 increased proton RBE in two TNBC cell lines, including MDA-MB-231 and Hs578T cells. Conversely, overexpression of cyclin D1 decreased the proton RBE in cyclin D1-deficient BT-549 cells. The depletion of cyclin D1 impaired proton-induced RAD51 foci formation in MDA-MB-231 cells. Taken together, this study provides important clues about the cyclin D1-CDK4-RB1 pathway as a potential target for proton beam therapy in TNBC.